A Comparison of Perioperative Blood Transfusions and Other Complications Following Transverse Rectus Abdominis Myocutaneous Flaps versus Deep Inferior Epigastric Perforator Flaps - Amaratunga, Rajith A.; Soliman, Bishoy; Lam, Thomas C. (Scientific Research, 2017)
Objective: Abdominal based free flaps such as the Transverse Rectus Abdominis Myocutaneous (TRAM) flap and Deep Inferior Epigastric Perforator (DIEP) flap are essential tools in the reconstructive armamentarium post mastectomy. These reconstructions are often prolonged, complex and associated with complications. This study aims to compare the complication rate, particularly focusing on perioperative transfusions, between TRAM and DIEP flaps performed by the senior author in our tertiary referral centre. Methods: A retrospective review was conducted of one hundred and seven consecutive TRAM and DIEP flaps from 2000 to 2014. The two groups were analysed for demographics, preoperative risk factors and post-operative complications including blood transfusions, haematomas, flap losses, redo-anastomoses, flap infections, abdominal wound sequelae and non-surgical complications. Results: Sixty-three patients underwent 67 free/muscle sparing TRAM flaps and 35 patients underwent 40 DIEP flaps. There were no statistically significant differences in patient demographics or preoperative risk factors between the two groups. Five TRAM flap cases (7.9%) required transfusion whilst no DIEP flap cases required transfusion. This difference was not found to be statistically significant (p = 0.16). However, free/muscle-sparing TRAM flaps were found to have a significantly higher overall complication rate compared to DIEP flaps (23.8% vs. 5.7%, p = 0.02). Conclusion: The current study demonstrated no difference in perioperative transfusion requirement between TRAM and DIEP cases. There was however a significantly higher rate of overall complications associated with TRAM flaps warranting the authors to conclude that care be taken when opting for this reconstructive method.
Keywords: Breast Reconstruction; DIEP; TRAM; Complications